Identifying targets for improvement using a nationally standardized survey: Surgical antimicrobial prophylaxis in orthopedic surgery. (25th December 2020) - Ierano, Courtney E.; Thursky, Karin; Marshall, Caroline; Koning, Sonia; James, Rodney; Johnson, Sandra; Imam, Nabeel; Worth, Leon J.; Peel, Trisha
Abstract: Background: Surgical antimicrobial prophylaxis (SAP) is commonly administered in orthopedic procedures. Research regarding SAP appropriateness for specific orthopedic procedures is limited and is required to facilitate targeted orthopedic prescriber behavior change. Objectives: To describe SAP prescribing and appropriateness for orthopedic procedures in Australian hospitals. Design, setting, and participants: Multicenter, national, quality improvement study with retrospective analysis of data collected from Australian hospitals via Surgical National Antimicrobial Prescribing Survey (Surgical NAPS) audits from January 1, 2016, to April 15, 2019, were analyzed. Methods: Logistic regression identified hospital, patient and surgical factors associated with appropriateness. Adjusted appropriateness was calculated from the multivariable model. Additional subanalyses were conducted on smaller subsets to calculate the adjusted appropriateness for specific orthopedic procedures. Results: In total, 140 facilities contributed to orthopedic audits in the Surgical NAPS, including 4, 032 orthopedic surgical episodes and 6, 709 prescribed doses. Overall appropriateness was low, 58.0% (n = 3, 894). This differed for prescribed procedural (n = 3, 978, 64.7%) and postprocedural doses (n = 2, 731, 48.3%). The most common reasons for inappropriateness, when prophylaxis was required, was timing for procedural doses (50.9%) and duration for postprocedural prescriptions (49.8%). The adjusted appropriateness of each orthopedic procedure group was low for procedural SAP (knee surgery, 54.1% to total knee joint replacement, 74.1%). The adjusted appropriateness for postprocedural prescription was also low (from hand surgery, 40.7%, to closed reduction fractures, 68.7%). Conclusions: Orthopedic surgical specialties demonstrated differences across procedural and postprocedural appropriateness. The metric of appropriateness identifies targets for quality improvement and is meaningful for clinicians. Targeted quality improvement projects for orthopedic specialties need to be developed to support optimization of antimicrobial use.